Effectiveness of structural equation modeling to measure hotel customer satisfaction - Siti Normi; Mangasa Panjaitan (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, 2022)
Although some studies on gauging hotel guests' levels of satisfaction have been published in several research findings, structural equation modeling's efficacy in Indonesia is still rarely investigated. The study's objective is to assess hotel patron satisfaction utilizing an electronic system for guest reviews that is centered on online and Internet technology. The research's data came from 500 hotel guests staying at two five-star full-service hotels in Medan, North Sumatra. To accomplish this goal, the study used structural equation modeling to uncover the inherent link between consumer assessments of hotel services and amenities on one side and perceived usefulness, contentment, and their intention to return and refer customers on the other side. The findings demonstrate the clear correlations between value, contentment, desire to return and suggest as well as customer ratings of employee quality of service, guest bedroom quality, safety, and service disruption. Additionally, it should be highlighted that major mediating influences had an impact on how well-liked the hotel's amenities and employees provided service to guests. Through the use of web-based technologies, the research offered several recommendations for improving guest satisfaction with hotel operations. The results of this study could contribute to hotel management concentrating on the elements of the experiences of their guests that are the most important factors for boosting the level of satisfaction.